Factors influencing hcp’s prescribing behaviour of nutrition formula in Malaysia hospital - Low, Yiing Jia (2023)
Malaysia’s total health expenditure increased 100% from RM32.9 billion in 2010 to RM64.3 billion in 2019. 55% of this expenditure was spent in hospitals, and public sector health expenditure was higher than private sector, which is 33.7 billion (52.5%) (Malaysia National Health Accounts Health Expenditure Report 1997-2019, 2021). Health expenditure is expected to reach RM91.1 billion by 2025 with 5-year compound annual growth rate of 7.6% (The Edge Market, 2022). In fact, the recent pandemic has also brought greater emphasis on health care and health care professionals. This study focuses on a more specific area of health and health care professionals, primarily focus on nutrition formula prescribed by health care professionals in the hospital setting of interest is how marketing and promotional strategies influence healthcare professional decisions amongst more specific influences. The following paragraphs will provide an overview of the different prescriptions and also the health care industry focusing on nutritional formula. After that the research objectives will be elaborated upon and chapter or organization will be provided.